2021
DOI: 10.1002/bio.4103
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the toxic effects and mechanism of methoxylated polybrominated diphenyl ethers (MeO‐PBDEs) on thyroxine‐binding globulin (TBG): Synergy between spectroscopic and computations

Abstract: The interaction mechanism between thyroxine-binding globulin (TBG) and three methoxylated polybrominated diphenyl ethers (MeO-PBDEs) was analyzed by steady-state fluorescence, ultraviolet-visible (UV-visible) spectroscopy, circular dichroism (CD), molecular docking and molecular dynamics simulation methods. The results of the molecular docking technique revealed that 2 0 -MeO-BDE-3, 5-MeO-BDE-47, and 3-MeO-BDE-100 combined with TBG at the active site. The steady-state fluorescence spectra displayed that MeO-PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A distinction could be made between the two mechanisms according to the relationship between the quenching constant ( K sv ) and temperature. The quenching type, binding constant, and binding site could be calculated using the Stem‐Volmer and double logarithmic curve equation 27,28 F0/Fgoodbreak=1goodbreak+KSV[]Qgoodbreak=1goodbreak+kqτ0[]Q log()F0goodbreak−F/Fgoodbreak=logitalicKagoodbreak+nlog[]Q …”
Section: Resultsmentioning
confidence: 99%
“…A distinction could be made between the two mechanisms according to the relationship between the quenching constant ( K sv ) and temperature. The quenching type, binding constant, and binding site could be calculated using the Stem‐Volmer and double logarithmic curve equation 27,28 F0/Fgoodbreak=1goodbreak+KSV[]Qgoodbreak=1goodbreak+kqτ0[]Q log()F0goodbreak−F/Fgoodbreak=logitalicKagoodbreak+nlog[]Q …”
Section: Resultsmentioning
confidence: 99%
“…Docking scores suggested that sulfated PBDEs have stronger affinity for TTR than the corresponding OH‐PBDEs. Free energy calculations indicated that van der Waals forces dominate the binding and residues Ser117 and Lys15 have important roles in determining the binding orientations of the ‐OSO 3 ‐ group of sulfated PBDEs. – Molecular docking suggested that 2’‐MeO‐BDE‐3, 5‐MeO‐BDE‐47 and 3‐MeO‐BDE‐100 bind to the thyroid hormone binding site of TBG (Huang et al., 2021b). Analysis with spectroscopic techniques together with free energy calculations indicated that the MeO‐PBDE combined with TBG primarily by hydrogen bonding and hydrophobic interactions and that van der Waals force is important.…”
Section: Assessmentmentioning
confidence: 99%
“…Molecular docking suggested that 2’‐MeO‐BDE‐3, 5‐MeO‐BDE‐47 and 3‐MeO‐BDE‐100 bind to the thyroid hormone binding site of TBG (Huang et al., 2021b ). Analysis with spectroscopic techniques together with free energy calculations indicated that the MeO‐PBDE combined with TBG primarily by hydrogen bonding and hydrophobic interactions and that van der Waals force is important.…”
Section: Assessmentmentioning
confidence: 99%